БИБЛИОТЕКА им. Ицика Мангера – сегодня - ISCHIMJI, Tatiana (BIBLIOPOLIS, 2020)
What is the I. Mangher Library-culture center today – after 25 years from the day of its opening? What is its mission, functions, and what kind of services the library provides to users? This article answers these questions.